Theoretical insights into the enantioselectivity and mechanism of diels-alder reactions involving chiral cationic oxazaborolidinium catalyst - Omar, N.Y.M.; Zain, Sharifuddin Md; Rahman, N.A. (2011)
The chiral oxazaborolidinium ion catalyzed Diels-Alder reaction between 2-methyl-1,3-butadiene and 2,3-dimethyl-1,4-benzoquinone was studied by means of density functional theory (DFT) at the B3LYP/6-31G(d) level of theory. Different DFT-based theoretical approaches including the reaction force, the natural population analysis of the charge transfer, the topological analysis of the electron localization function (ELF), and the global and local reactivity indices were applied to investigate and rationalize the mechanism and the endo/exo selectivity of this reaction. The changes in the physical and chemical properties of the reacting molecules along the intrinsic reaction coordinate (IRC) were also monitored to shed light on the mechanistic details. The analysis of the studied Diels-Alder reaction within the framework of DFT revealed and explained the preference of the endo path to the exo channel, and pointed out a concerted but highly asynchronous reaction mechanism. © 2011 The Chemical Society of Japan.